Anode for lithium ion battery, lithium ion battery, method for manufacturing anode for lithium ion battery, and method for manufacturing lithium ion battery
The integration of hydrophobic cellulose with Si particles and an organic solvent-based binder in the negative electrode of lithium-ion batteries addresses the issue of volume expansion and moisture reactivity, resulting in improved capacity and cycle life.
Patent Information
- Application Number
- JP2020216634
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-25
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2040-12-25
AI Technical Summary
Lithium-ion batteries using silicon (Si) as the negative electrode active material face challenges due to the volume expansion of Si during lithium insertion, leading to detachment of Si particles from the electrode and resulting in low cycle characteristics and battery life.
A negative electrode for lithium-ion batteries is developed, comprising a negative electrode mixture with Si particles, an organic solvent-based binder, and hydrophobic cellulose. The hydrophobic cellulose is derived from cellulose nanofibers where part of the hydrophilic group is replaced by a hydrophobic group, enhancing the binding properties and reducing moisture reactivity.
The proposed solution improves battery characteristics by enhancing the capacity and cycle life of lithium-ion batteries, while also preventing the adverse effects of moisture on the battery performance.
Smart Images

Figure 0007671580000005 
Figure 0007671580000006 
Figure 0007671580000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a negative electrode for a lithium ion battery, a lithium ion battery, a method for producing a negative electrode for a lithium ion battery, and a method for producing a lithium ion battery. [Background technology]
[0002] The fields in which secondary batteries are used are expanding from electronic devices to automobiles and large-scale power storage systems, and among them, lithium-ion batteries (secondary batteries) are attracting attention because they can be made small and lightweight and have high energy density.
[0003] The negative electrode in a lithium ion battery is composed of a current collector and a negative electrode mixture layer provided on the current collector. The negative electrode mixture layer contains a binder and the like in addition to a negative electrode active material.
[0004] For example, Patent Document 1 discloses a non-aqueous binder for electrodes of lithium ion batteries that is a composite of cellulose nanofibers and thermoplastic fluorine-based resin, in which the cellulose nanofibers are cellulose having a fiber diameter of 0.002 μm or more and 1 μm or less, a fiber length of 0.5 μm or more and 10 mm or less, and an aspect ratio (fiber length of cellulose nanofiber / fiber diameter of cellulose nanofiber) of 2 or more and 100,000 or less. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2019 / 064583 Summary of the Invention [Problem to be solved by the invention]
[0006] Various materials are being investigated for the negative electrode of lithium-ion batteries in order to increase their capacity. Among them, silicon (Si) has a higher theoretical capacity than graphite and is considered a promising material for the negative electrode active material.
[0007] However, since the volume of this Si expands as lithium is inserted, repeated charging and discharging of the battery causes the negative electrode active material to repeatedly expand and contract, which causes the Si (particles) to easily peel off from the electrode, resulting in poor cycle characteristics (shortening battery life).
[0008] In response to these issues, it has been studied to reduce the effect of volume expansion by nano-sizing (refining) Si. On the other hand, the negative electrode is formed by adding the negative electrode active material and binder to a solvent to form a slurry, which is then applied to a current collector. In this case, when Si is nano-sized (refined), the surface area of the Si nanoparticles (nano-Si) increases, and a large amount of binder is required to bind the nano-Si together. In addition, Si reacts with moisture, and when a water-based binder is used, hydrogen gas is generated, which reduces the battery characteristics (issue 1). Even when an organic binder is used, the increased amount of binder reduces the cycle characteristics (shortens the battery life) (issue 2).
[0009] Therefore, an object of one embodiment of the present specification is to provide an anode capable of improving battery characteristics such as high capacity and cycle characteristics (battery life) of a battery, and a lithium ion battery using the anode, and to provide a method for manufacturing an anode and a lithium ion battery capable of improving battery characteristics such as high capacity and cycle characteristics (battery life).
[0010] The above and other objects and novel features of the present invention will become apparent from the description of this specification and the accompanying drawings. [Means for solving the problem]
[0011] The negative electrode for a lithium ion battery disclosed in the present application has a negative electrode mixture having a negative electrode active material, a binder, and hydrophobized cellulose, the negative electrode active material containing Si particles, the binder being an organic solvent-based binder, and the hydrophobized cellulose being cellulose in which some of the hydrophilic groups have been replaced with hydrophobic groups.
[0012] The lithium ion battery disclosed in the present application is a lithium ion battery comprising: a negative electrode having a current collector and a negative electrode mixture layer formed on the current collector; a positive electrode; and an electrolyte solution, wherein the negative electrode mixture layer contains a negative electrode active material, a binder, and hydrophobized cellulose, the negative electrode active material contains Si particles, the binder is an organic solvent-based binder, and the hydrophobized cellulose is cellulose in which some of the hydrophilic groups have been substituted with hydrophobic groups.
[0013] The method for producing a negative electrode for a lithium ion battery disclosed in the present application includes the steps of: (a) mixing a negative electrode active material, a binder, and hydrophobized cellulose to form a negative electrode slurry; and (b) applying the negative electrode slurry onto a current collector, wherein the negative electrode active material contains Si particles, the binder is an organic solvent-based binder, and the hydrophobized cellulose is cellulose in which some of the hydrophilic groups have been replaced with hydrophobic groups.
[0014] The method for producing a lithium ion battery disclosed in the present application includes: (a) preparing a negative electrode slurry; (b) applying the negative electrode slurry onto a current collector to form a negative electrode having the current collector and a negative electrode mixture layer; (c) forming an electrode group in which the negative electrode and a positive electrode are stacked with a separator interposed therebetween; (d) housing the electrode group in a battery container; and (e) after the step (d), injecting an electrolyte into the battery container. The step (a) is a step of mixing a negative electrode active material, a binder, and hydrophobized cellulose to form a negative electrode slurry, the negative electrode active material containing Si particles, the binder being an organic solvent-based binder, and the hydrophobized cellulose being cellulose in which some of the hydrophilic groups have been replaced with hydrophobic groups. Effect of the Invention
[0015] The effects obtained by a representative embodiment of the present specification will be briefly described below.
[0016] According to the negative electrode for a lithium ion battery disclosed in an embodiment of this specification, it is possible to improve battery characteristics such as a high capacity battery and cycle characteristics (battery life).
[0017] According to the lithium ion battery disclosed in an embodiment of this specification, it is possible to improve battery characteristics such as a high battery capacity and cycle characteristics (battery life).
[0018] According to the method for producing a positive electrode for a lithium ion battery disclosed in one embodiment of the present specification, it is possible to produce a negative electrode that can increase the capacity of the battery and improve battery characteristics such as cycle characteristics (battery life).
[0019] According to the method for manufacturing a lithium ion battery disclosed in an embodiment of this specification, it is possible to manufacture a lithium ion battery with improved battery characteristics, such as a high battery capacity and cycle characteristics (battery life). [Brief description of the drawings]
[0020] [Figure 1] FIG. 1 is a diagram showing a schematic configuration of a positive electrode, a negative electrode and a lithium ion battery using these electrodes according to a first embodiment. [Diagram 2] FIG. 1 is a diagram showing a schematic configuration of a positive electrode, a negative electrode and a lithium ion battery using these electrodes according to a first embodiment. [Diagram 3] FIG. 1 shows the preparation process of hydrophobized CeNFs (cellulose nanofibers) dispersed in a solvent. [Figure 4] FIG. 2 is a diagram showing an example of a process for preparing a negative electrode slurry. [Diagram 5] FIG. 2 is a schematic diagram showing the configuration of a negative electrode manufacturing apparatus according to the first embodiment. [Figure 6]FIG. 2 is a perspective view showing application of negative electrode slurry using a slit die. [Figure 7] FIG. 1 is a diagram showing an example of a process for preparing a negative electrode slurry when a water-based binder is used. [Figure 8] 1 is a graph showing initial characteristics of a coin battery. [Figure 9] 1 is a graph showing initial characteristics of a battery using an aqueous solvent. [Figure 10] 1 is a graph showing cycle characteristics of coin batteries (samples 1, 2, 5, and 6). [Figure 11] 1 is a graph showing cycle characteristics of coin batteries with different amounts of hydrophobized CeNF added. [Figure 12] 1 is a graph showing the cycle characteristics of a coin battery in which the ratio of nano-Si is 8:2. [Figure 13] FIG. 1 is a cross-sectional perspective view showing the configuration of a cylindrical lithium ion battery. [Figure 14] FIG. 2 is a cross-sectional view showing a method for preparing a negative electrode slurry using an extruder. [Figure 15] FIG. 2 is a cross-sectional view showing a method for preparing a positive electrode slurry using an extruder. [Figure 16] FIG. 1 shows the preparation process of hydrophobized CeNFs dispersed in an organic solvent. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] Hereinafter, the embodiments will be described in detail with reference to examples and drawings. In all the drawings for explaining the embodiments, the same reference numerals are used for members having the same functions, and the repeated explanations will be omitted. In addition, when a range is indicated as A to B in the following embodiments, it means A or more and B or less, unless otherwise specified.
[0022] (Embodiment 1) 1 and 2 are schematic diagrams showing the configurations of the negative electrode, positive electrode, and lithium-ion battery using these electrodes according to the present embodiment. Fig. 1(A) shows the configuration of the negative electrode, Fig. 1(B) shows the configuration of the positive electrode, and Fig. 1(C) shows the internal configuration of the lithium-ion battery.
[0023] As shown in FIG. 1(A), the negative electrode is composed of a current collector 1S and a negative electrode mixture layer 1M provided thereon, and as shown in FIG. 1(B), the positive electrode is composed of a current collector 2S and a positive electrode mixture layer 2M provided thereon. As shown in FIG. 1(C), the lithium ion battery has a negative electrode, a positive electrode, and a separator disposed therebetween, and the negative electrode and the positive electrode are disposed opposite each other so that the negative electrode mixture layer 1M and the positive electrode mixture layer 2M are in contact with the separator SP (see also FIG. 2). As shown in FIG. 1(C), a part of the current collector 1S of the negative electrode becomes a negative electrode terminal 1T, and a part of the current collector 2S of the positive electrode becomes a positive electrode terminal 2T. The laminate (also called an electrode group) of the negative electrode, the positive electrode, and the separator is accommodated in a battery container (such as a bag made of a laminate film, a battery can, etc.) together with an electrolyte, and is sealed in a state in which the negative electrode terminal 1T and the positive electrode terminal 2T are protruding (exposed).
[0024] Such negative and positive electrodes are formed by adding each electrode material such as an electrode active material and a binder to a solvent (such as an organic solvent or an aqueous solvent) to form a slurry, which is then applied onto a current collector and dried.
[0025] In this embodiment, nano-Si is used as the negative electrode active material in the negative electrode mixture layer. In addition, a binder is used in the negative electrode mixture layer to bind the negative electrode active material and the like. In addition, hydrophobized cellulose is used as an additive in the negative electrode mixture layer.
[0026] By using such a negative electrode mixture layer, it is possible to improve battery characteristics such as high capacity and cycle characteristics (battery life). In particular, even when nano-Si and an organic solvent binder are used, it is possible to improve battery characteristics such as high capacity and cycle characteristics (battery life).
[0027] Next, the negative electrode, positive electrode, separator, and electrolyte of the lithium ion battery of this embodiment will be described in order.
[0028] [Negative electrode] As described above, the negative electrode (negative electrode plate, negative electrode sheet) has a current collector and a negative electrode mixture layer provided thereon. The negative electrode mixture layer is a layer including at least a negative electrode active material provided on the current collector. In the present embodiment, the negative electrode mixture layer contains nano-Si as the negative electrode active material. The negative electrode mixture layer also contains a binder for binding the negative electrode active material. Furthermore, the negative electrode mixture layer contains hydrophobized cellulose as an additive. The negative electrode mixture layer may contain other additives such as a thickener, a dispersant, and a conductive agent (also called a conductive assistant).
[0029] A metal thin film can be used as the current collector for the negative electrode. Metal materials that can be used include copper, lithium (Li), stainless steel, etc. Furthermore, the surfaces of these materials may be plated with nickel or the like.
[0030] (Negative electrode active material) The negative electrode active material can be nano-Si, which is a Si (silicon)-based material. This nano-Si is made of Si particles on the order of nanometers. SiO (SiOx) may be formed on the Si surface, or carbon-coated nano-Si may be used. The thickness of the coating layer is preferably about 1 μm to 10 nm.
[0031] There is no limit to the method of miniaturizing (nanofiberizing) Si. For example, fine particles of Si can be obtained by vaporizing a Si compound and then cooling it. The average particle size (median diameter, D50) of nano-Si is preferably 10 nm to 500 nm, more preferably 20 nm to 200 nm. In general, the finer the particle size of Si, the higher the electrode capacity can be. However, on the other hand, since the surface area of Si increases, it is necessary to increase the amount of binder to prevent peeling due to expansion and contraction during charging and discharging. Therefore, it is preferable to select the particle size according to the battery capacity to be manufactured. The average particle size (median diameter, D50) of nano-Si can be measured, for example, by a laser diffraction / scattering particle size distribution measurement method. In addition, Si particles can be observed using an electron microscope such as SEM or TEM, or an atomic force microscope such as AFM or SPM, and the particle size can also be measured by this observation.
[0032] As the negative electrode active material, nano-Si may be used in combination with the following other materials. As the negative electrode active material that can be used in combination with nano-Si, carbon-based materials such as graphite, hard carbon (hardly graphitizable carbon), and soft carbon (easily graphitizable carbon) can be used. In addition, lithium titanate (Li4Ti5O 12 From the viewpoint of improving cycle characteristics, it is preferable to use a carbon-based material, particularly graphite, in combination.
[0033] As described above, by using nano-Si as the negative electrode active material, theoretically the capacity should be increased, but in the end the battery capacity does not increase much, and the cycle characteristics tend to decrease. As described above, this is thought to be due to the increase in the binder caused by the increase in the surface area of the particles based on the nano-ization of the particles to reduce the effect of the volume expansion of Si. However, in this embodiment, by adding hydrophobic CeNF, the decrease in the battery capacity can be suppressed even if the binder is increased, and the inherent battery capacity increase effect of Si can be brought out. This is thought to be due to the suppression of the volume expansion of Si by the composite of hydrophobic CeNF and the binder. In addition, it is thought that such suppression of the volume expansion suppresses the peeling of the negative electrode active material, and improves the cycle characteristics (battery life).
[0034] (Binder) The binder has a role of binding the negative electrode materials such as the electrode active material in the negative electrode mixture layer together, and binding the negative electrode material to the current collector, etc. Binders for the electrode mixture layer can be divided into aqueous and organic solvent-based.
[0035] Examples of aqueous binders include styrene-butadiene copolymer rubber (SBR), polyvinyl alcohol, polyacrylic acid, and carboxymethyl cellulose, and are used in a state dispersed in an aqueous solvent (e.g., water).
[0036] Examples of organic solvent binders include polyvinylidene fluoride (PVdF) and polyimide (PI), which are used in a state added to an organic solvent. Of these, polyvinylidene fluoride (PVdF) is called a soluble binder and is used in a state dissolved in an organic solvent such as N-methyl-2-pyrrolidone (NMP). Polyimide (PI) is called a reactive binder, and is used in a state where a PI precursor is dissolved or dispersed in a solvent such as NMP, and then heated to cause a crosslinking reaction through imidization (dehydration reaction and cyclization reaction), resulting in a tough PI.
[0037] In this embodiment, an organic solvent-based binder is used. As described later, when a water-based binder is used, hydrogen gas is generated by the reaction between water and Si, and the electrode characteristics are deteriorated (see FIG. 9). In this way, by using an organic solvent-based binder, the reaction between water and Si can be prevented and the electrode characteristics can be improved.
[0038] Furthermore, normally, the use of nano-Si requires the addition of a large amount of organic solvent-based binder, which reduces the battery capacity and cycle characteristics (battery life). However, in this embodiment, by adding hydrophobic CeNF as an additive, the battery capacity and cycle characteristics (battery life) can be improved even when an organic solvent-based binder is used (see Figures 10, 11, etc.).
[0039] (Hydrophobic Cellulose) Cellulose (Cell-OH) is (C 12 H 20 O 10 ) n It is a carbohydrate represented by the following chemical structure (Chemical formula 1).
[0040] [ka]
[0041] As shown in the following chemical structure (Chemical Formula 2), 12 H 20 O 10 ) n Some of the hydroxyl groups of carbohydrates represented by the formula (R represents a divalent hydrocarbon group) ) substituted cellulose may also be used.
[0042] [ka]
[0043] As can be seen from the above chemical structural formulas (Chemical Formula 1 and Chemical Formula 2), cellulose has hydroxyl groups (hydrophilic groups). These hydroxyl groups (hydrophilic groups) are hydrophobized (lipophilized) using a hydrophobizing agent (e.g., a carboxylic acid compound). That is, the hydroxyl groups (-OH) of cellulose are substituted with hydrophobic groups. Specifically, some of the hydroxyl groups of cellulose are esterified with a carboxylic acid compound (R-CO-OH). In other words, the hydroxyl groups (-OH) of cellulose are converted into ester bonds (-O-CO-R, carboxyl groups). It is not necessary for all of the hydroxyl groups of cellulose to be substituted with hydrophobic groups, as long as some of them are substituted. An example of an esterification (hydrophobization) reaction of cellulose is shown in the following reaction formula.
[0044] [ka]
[0045] The hydrophobizing agent is not particularly limited as long as it has a composition capable of imparting hydrophobic groups to the hydrophilic groups of cellulose, and for example, a carboxylic acid compound can be used. Among them, it is preferable to use a compound having two or more carboxyl groups, an acid anhydride of a compound having two or more carboxyl groups, etc. Among the compounds having two or more carboxyl groups, it is preferable to use a compound having two carboxyl groups (dicarboxylic acid compound).
[0046] Examples of compounds having two carboxy groups include dicarboxylic acid compounds such as propanedioic acid (malonic acid), butanedioic acid (succinic acid), pentanedioic acid (glutaric acid), hexanedioic acid (adipic acid), 2-methylpropanedioic acid, 2-methylbutanedioic acid, 2-methylpentanedioic acid, 1,2-cyclohexanedicarboxylic acid, 2-butenedioic acid (maleic acid, fumaric acid), 2-pentenedioic acid, 2,4-hexadienedioic acid, 2-methyl-2-butenedioic acid, 2-methyl-2-pentenedioic acid, 2-methylidenebutanedioic acid (itaconic acid), benzene-1,2-dicarboxylic acid (phthalic acid), benzene-1,3-dicarboxylic acid (isophthalic acid), benzene-1,4-dicarboxylic acid (terephthalic acid), and ethanedioic acid (oxalic acid). Examples of the acid anhydride of a compound having two carboxy groups include dicarboxylic acid compounds such as maleic anhydride, succinic anhydride, phthalic anhydride, glutaric anhydride, adipic anhydride, itaconic anhydride, pyromellitic anhydride, and 1,2-cyclohexanedicarboxylic anhydride, and acid anhydrides of compounds containing multiple carboxy groups. Examples of the derivatives of the acid anhydride of a compound having two carboxy groups include those in which at least a part of the hydrogen atoms of the acid anhydride of a compound having a carboxy group is replaced with a substituent (e.g., an alkyl group, a phenyl group, etc.), such as dimethylmaleic anhydride, diethylmaleic anhydride, and diphenylmaleic anhydride. Among these, maleic anhydride, succinic anhydride, and phthalic anhydride are preferred because they are easily industrially applicable and easily gasified.
[0047] Furthermore, after the hydrophilic groups of cellulose are subjected to a hydrophobic treatment (modification with a carboxylic acid compound), a treatment for improving hydrophilicity may be carried out secondarily by adding an alkylene oxide. In addition, two or more kinds of the above-mentioned hydrophobizing agents may be added.
[0048] Cellulose may also be refined (nanofibrated) by defibration. Defibration (refining) can be done by chemical or mechanical methods. A combination of these methods may also be used. This type of defibration (refining) can produce CeNF with a fiber length (L) of 3 nm or more and 10 μm or less, and an aspect ratio (length L / diameter D) of 0.005 or more and 10,000 or less. Cellulose fibers refined to nanometer sizes in this way are called cellulose nanofibers (CeNF).
[0049] The above-mentioned pulverization (nanofiberization) of cellulose may be carried out before or after the hydrophobization.
[0050] (Preparation method of hydrophobized CeNF dispersed in a solvent) The hydrophobized CeNF is preferably used in a state dispersed in a solvent in order to prevent aggregation and to increase dispersibility in the slurry.
[0051] Figure 3 is a diagram showing the preparation process of hydrophobized CeNF dispersed in a solvent. For example, as shown in Figure 3, cellulose (solid, e.g., powder) and succinic anhydride (solid, e.g., tablet form) are mixed at 100°C or higher. For example, they are mixed at 125°C for 20 minutes using a pressure kneader. The weights of cellulose and succinic anhydride are, for example, 90 wt% (weight %, mass %) and 10 wt%.
[0052] The mixture is stirred under heating as described above, and an ester reaction occurs to produce hydrophobic cellulose. After this, the mixture is washed with acetone or the like to remove unreacted succinic anhydride.
[0053] Next, the produced hydrophobic cellulose is dispersed in an aqueous solvent (water and / or alcohols, etc., here water (HO)) and subjected to a micronization process (fibrillation process, nanoization). For example, a micronization device (Starburst) is used to perform a process at 245 MPa and 10 passes to nanonize the cellulose. This allows the production of hydrophobic CeNF dispersed in an aqueous solvent (e.g., water).
[0054] (Preparation of negative electrode slurry) Next, the preparation process of the negative electrode slurry will be described. The negative electrode slurry is prepared by adding the above-mentioned negative electrode active material, organic solvent binder, and hydrophobized CeNF (dispersed in water) to an organic solvent. In addition to the above, other additives such as a conductive agent and a dispersant may be further added. FIG. 4 is a diagram showing an example of the preparation process of the negative electrode slurry. An example of the preparation process of the negative electrode slurry will be described with reference to FIG. 4.
[0055] First, prepare mixed solution 1 by mixing an organic solvent binder, an organic solvent, and hydrophobic CeNF (dispersed in water). At this time, other additives such as a conductive agent and a dispersant may be further added. Stir this mixed solution 1 (for example, stir at 1000 rpm for about 1 minute). A high-speed stirrer (for example, a homodisper) can be used for stirring.
[0056] Next, graphite and nano-Si are added as negative electrode active materials to the mixed solution 1, and further, for example, CNT and acetylene black (AB) are added as conductive agents, followed by stirring to prepare the mixed solution 2. A high-speed stirrer (for example, Homo Disper) is used for stirring, and the mixture is stirred at 3000 rpm for, for example, about 30 minutes.
[0057] Next, alcohol is added to the mixed solution 2 and then stirred to prepare the mixed solution 3. A high-speed stirrer (for example, Homo Disper) is used for stirring, and the mixture is stirred at 3000 rpm for about 1 minute, for example.
[0058] In this way, the negative electrode slurry can be obtained. The viscosity of the negative electrode slurry obtained in this way is 6200 mPas (35°C), and bubbles like those in the negative electrode slurry 4 described later could not be visually confirmed. In addition, the coating property is good, and for example, when the negative electrode mixture layer is formed by the device described later, defects due to bubbles or the like were not confirmed in the layer. The viscosity of the negative electrode slurry is preferably 3000 to 5000 mPas in consideration of the coating property.
[0059] In this manner, in the present embodiment, by using an organic solvent-based binder, it is possible to reduce air bubbles generated in the negative electrode slurry and improve the characteristics of the negative electrode mixture layer.
[0060] As the conductive agent, which is the other additive, in addition to the above-mentioned AB and CNT, Ketjen black, carbon nanofiber, etc. can be used. As the dispersant, a surfactant can be used. As the other additive, in addition to the dispersant, a thickener, etc. may be used.
[0061] (Negative electrode formation process) The negative electrode slurry is applied to the surface of a current collector (e.g., steel foil) and dried to form a negative electrode mixture layer. In this manner, a negative electrode having a current collector (e.g., steel foil) and a negative electrode mixture layer can be formed (see FIG. 1(A)).
[0062] There is no limitation on the method of applying the negative electrode slurry, but for example, a die coater can be used. Then, by drying the applied layer, a negative electrode mixture layer can be formed on the surface of the substrate S. In this way, a negative electrode having the substrate (for example, steel foil as a current collector) S and the negative electrode mixture layer can be formed.
[0063] FIG. 5 is a schematic diagram showing the configuration of a manufacturing apparatus for a negative electrode according to the present embodiment. The manufacturing apparatus shown in FIG. 5 has an unwinding section (unloading section) UW that unwinds the substrate (current collector) S, and a winding section (loading section) WD that winds the substrate (current collector) S. The substrate (current collector) S is continuously arranged from the unwinding section UW to the winding section WD, and a negative electrode mixture layer (a coating layer of negative electrode slurry SL) 1M is formed on the surface (first surface) of the substrate S between the unwinding section UW and the winding section WD, completing the negative electrode. According to this manufacturing apparatus, the substrate S in a roll shape (wound strip shape) can be continuously processed, and the negative electrode can be efficiently formed. In this specification, the unwinding section UW side may be referred to as the upstream side, and the winding section WD may be referred to as the downstream side.
[0064] Specifically, at least one coating section 20 and drying section (drying oven) 30 are disposed between the unwinding section UW and the winding section WD. The substrate S is processed in each processing section while being guided by a plurality of rolls (guide rolls) R, and a negative electrode mixture layer (a coating layer of negative electrode slurry SL) 1M is formed on the surface of the substrate S. This will be described in detail below.
[0065] The substrate S unwound from the unwinding section UW is guided by a plurality of rolls R and transported to the coating section 20. The coating section 20 is provided with a coating liquid tank T, a pump P, and a slit die D. A negative electrode slurry SL, which is a coating liquid, is supplied to the slit die D from the coating liquid tank T via the pump P. A valve B is provided between a supply pipe for the negative electrode slurry SL and the coating liquid tank T. FIG. 6 is a perspective view showing the application of the negative electrode slurry using the slit die. As shown in FIG. 6, the negative electrode slurry SL is applied onto the substrate S from a manifold inside the slit die D through a slit (discharge section) at the tip of the die, and a coating layer (SL) is formed.
[0066] The substrate S on which the coating layer (SL) is formed is guided by a roll R and transported to the drying section 30. In the drying section 30, heated air is introduced from a nozzle (not shown). The temperature of the heated air is controlled by a heating section (heater, etc.) (not shown). The temperature of the drying section 30 is 100° C. or lower, for example, about 70° C. In this drying section 30, the liquid component of the coating layer (SL) is vaporized to form the negative electrode mixture layer 1M.
[0067] In this way, by using the negative electrode slurry SL, a high-precision negative electrode can be efficiently formed. In particular, the negative electrode slurry SL has few bubbles and has good coatability, and a good negative electrode can be formed even if the feed speed of the substrate S is 10 m / min or more.
[0068] A rolling section may be provided downstream of the drying section 30. For example, the coating layer can be rolled by passing the laminate of the substrate S and the coating layer through a narrow gap between two rolls. The rolling section may be provided between the coating section 20 and the drying section 30.
[0069] A gravure coater may be used instead of the die coater. The negative electrode slurry SL may be applied to both sides of the substrate S. In this case, the negative electrode slurry SL may be applied to each side of the substrate S in sequence, or the negative electrode slurry SL may be applied to both sides of the substrate S during the process shown in FIG.
[0070] FIG. 7 shows an example of a process for preparing a slurry for a negative electrode when a water-based binder is used. As shown in FIG. 7, a mixed solution 1 is prepared by mixing a water-based binder and water. At this time, other additives such as a conductive agent and a dispersant may be further added. This mixed solution 1 is stirred (for example, stirred at 1000 rpm for about 1 minute). A high-speed stirrer (for example, a homodisper) can be used for stirring.
[0071] Next, graphite, nano-Si, and other negative electrode active materials (e.g., acetylene black (AB)) are added as negative electrode active materials to the mixed solution 1, and then stirred to prepare the mixed solution 2. A high-speed stirrer (e.g., Homo Disper) is used for stirring, and the mixture is stirred at 1000 to 4000 rpm for about 30 minutes, for example.
[0072] Next, alcohol is added to the mixed solution 2 and then stirred to prepare the mixed solution 3. A high-speed stirrer (for example, Homo Disper) is used for stirring, and the mixture is stirred at 1000 to 4000 rpm for about 1 minute, for example.
[0073] [Positive electrode] As described above, the positive electrode (positive electrode plate, positive electrode sheet) has a current collector and a positive electrode mixture layer provided thereon. The positive electrode mixture layer is a layer provided on the current collector and contains at least a positive electrode active material.
[0074] As the positive electrode active material, for example, a ternary metal oxide lithium such as NCA (lithium nickel cobalt aluminum oxide, lithium nickel-cobalt-aluminate (Li(Ni,Co,Al)O2)) or NCM (lithium nickel cobalt manganese oxide, lithium nickel-cobalt-manganese oxide (Li(Ni,Co,Mn)O2)) can be used. The positive electrode mixture layer contains a binder for binding the positive electrode active material. As the binder, for example, a plastic fluorine-based resin binder such as polyvinylidene fluoride (PVdF) can be used. As in the case of the negative electrode, the positive electrode mixture layer may contain a conductive agent, a thickener, a dispersant, etc.
[0075] A metal thin film can be used as the current collector for the positive electrode. Aluminum, stainless steel (SUS), etc. can be used as the metal material. In addition, these materials may be plated with nickel or the like. In the examples described later, evaluation was performed using a half cell (counter electrode is Li metal) without a positive electrode.
[0076] [Separator] The separator may be made of a resin such as polypropylene (PP), polyethylene (PE), or polyethylene terephthalate (PET), glass fiber, or nonwoven fabric.
[0077] [Electrolyte] The electrolyte solution is composed of an electrolyte salt and an electrolyte solvent. A lithium salt can be used as the electrolyte salt. Among them, at least one selected from the group consisting of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium trifluoromethanesulfonate (LiCF3SO4), lithium bistrifluoromethanesulfonylimide (LiN(SO2CF3)2), lithium bispentafluoroethanesulfonylimide (LiN(SO2C2F5)2), lithium bisoxalateborate (LiBC4O8), and the like can be used. As the electrolyte solvent, for example, at least one selected from the group consisting of propylene carbonate (PC), ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), diphenyl carbonate, γ-butyrolactone (GBL), γ-valerolactone, methyl formate (MF), 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, dimethoxyethane (DME), 1,2-diethoxyethane, diethyl ether, sulfolane, tetrahydrofuran (THF), methylsulfolane, nitromethane, N,N-dimethylformamide, dimethylsulfoxide, vinylene carbonate (VC), vinylethylene carbonate (EVC), fluoroethylene carbonate (FEC), and ethylene sulfite (ES) can be used. In particular, it is preferable to use a mixture of the above-mentioned cyclic carbonates such as EC and PC and chain carbonates such as DMC, DEC and EMC. In the mixing ratio of these, for example, the proportion of the cyclic carbonate can be adjusted to the range of 10 to 90% by volume. Among these, it is preferable to use a mixture further containing VC, EVC, FEC, or ES.
[0078] [Example] Hereinafter, the present embodiment will be described in detail based on examples. However, the following examples are merely examples, and the present invention is not limited to the following examples.
[0079] <Sample 1> (Preparation of negative electrode slurry 1) A slurry for the negative electrode was prepared according to the above-mentioned "Step of preparing a slurry for the negative electrode".
[0080] First, the binder (PI dissolved in NMP, 11 wt%) and hydrophobized CeNF (dispersed in water, solid component concentration 0.5 wt%, acid value: 76.5 mg / g) were mixed at a rotation speed of 1000 rpm using a homodisper. The hydrophobized CeNF was dispersed in water and had an acid value of 76.5 mg / g. The amount of hydrophobized CeNF added was adjusted so that the ratio of the solid component in the negative electrode slurry 1 (i.e., the portion that becomes the negative electrode mixture) was 0.5 wt%. The concentration of hydrophobized CeNF in the aqueous dispersion was 4 wt%. The acid value is expressed in mg of potassium hydroxide required to neutralize the acidic component contained in 1 g of sample, and can be adjusted in the range of, for example, 30 to 300 mg / g.
[0081] Next, graphite and nano-Si, which are negative electrode active materials, were added in a weight ratio of 9:1, and carbon nanotubes (CNTs) were added as another negative electrode active material. The mixture was mixed for 24 minutes at a rotation speed of 3000 rpm in a homodisper. The amounts of graphite, nano-Si, and CNTs added were 78.3 wt%, 8.7 wt%, and 2 wt%, respectively. After this, alcohol was added and the mixture was stirred for 1 minute to obtain negative electrode slurry 1. The amounts of the negative electrode materials added are shown in Table 1.
[0082] In this example, nano-Si coated with carbon was used (average particle size: 45 nm, coating thickness: 2 to 3 nm). Graphite with an average particle size of 22 μm was used.
[0083] (Preparation of negative electrode 1) A negative electrode was produced according to the above-mentioned "negative electrode forming process". The negative electrode slurry 1 was applied to a current collector using a die coater, and dried in a drying furnace at 70° C. A Ni-plated steel foil was used as the current collector.
[0084] (Creating Battery 1) The negative electrode 1 thus prepared was combined with a Li metal counter electrode and a 100 μm thick glass fiber (separator) to prepare a half-cell coin-type battery (sample 1). The electrolyte used was 1 mol / L LiPF6 (EC:DEC=1:1 Vol%, VC:1 wt%). The coin-type battery is constructed by placing a stack (also called an electrode group) of the Li metal, negative electrode and separator in a coin-type can, injecting the electrolyte, and then closing and sealing the can. For example, the stack is arranged so that the Li metal is in contact with the bottom of the can and the negative electrode is in contact with the back surface of the lid.
[0085] <Sample 2> (Preparation of negative electrode slurry 2) Anode slurry 2 was prepared in the same manner as anode slurry 1, except that the binder (PI dissolved in NMP) in the aforementioned anode slurry 1 was reduced from 11 wt% to 5 wt%, with the difference being adjusted so that the graphite and nano-Si were 9:1.
[0086] (Preparation of negative electrode 2) Negative electrode 2 was prepared in the same manner as for negative electrode 1 described above.
[0087] (Creating Battery 2) Using the prepared negative electrode 2, a battery 2 was prepared in the same manner as the battery 1.
[0088] <Sample 3> (Preparation of negative electrode slurry 3) A negative electrode slurry 3 was prepared in the same manner as the negative electrode slurry 1, except that the ratio of graphite to nano-Si in the negative electrode slurry 1 was adjusted to 8:2.
[0089] (Preparation of negative electrode 3) Negative electrode 3 was prepared in the same manner as for negative electrode 1 described above.
[0090] (Creating Battery 3) Using the prepared negative electrode 3, a battery 3 was prepared in the same manner as the battery 1.
[0091] <Sample 4> (Preparation of negative electrode slurry 4) Anode slurry 4 was prepared by changing the binder of the above-mentioned anode slurry 1 to an aqueous one (here, 11 wt% SBR dispersed in water) and not adding hydrophobized CeNF. When using an aqueous binder, it was difficult to add a large amount of nano-Si, so anode slurry 4 was prepared by replacing a part of it with SiO. Specifically, nano-Si was 4 wt%, SiO was 8.5 wt%, graphite was 81 wt%, and acetylene black (AB) was 2 wt% as another anode active material. Air bubbles were confirmed in anode slurry 4.
[0092] (Preparation of negative electrode 4) Negative electrode 4 was prepared in the same manner as for negative electrode 1 described above.
[0093] (Creating Battery 4) Using the prepared negative electrode 4, a battery 4 was prepared in the same manner as the battery 1.
[0094] <Sample 5> (Preparation of negative electrode slurry 5) Negative electrode slurry 5 was prepared in the same manner as negative electrode slurry 1, except that the binder (PI dissolved in NMP) in the aforementioned negative electrode slurry 1 was reduced from 11 wt% to 7 wt%, with the difference being adjusted so that the graphite and nano-Si were 9:1.
[0095] (Preparation of negative electrode 5) Negative electrode 5 was prepared in the same manner as in the case of negative electrode 1 described above.
[0096] (Creating Battery 5) Using the produced negative electrode 5, a battery 5 was produced in the same manner as the battery 1.
[0097] <Sample 6> (Preparation of negative electrode slurry 6) Negative electrode slurry 6 was prepared in the same manner as negative electrode slurry 1, except that the binder (PI dissolved in NMP) in the aforementioned negative electrode slurry 1 was reduced from 11 wt% to 9 wt%, with the difference being adjusted so that the graphite and nano-Si were 9:1.
[0098] (Preparation of negative electrode 6) Negative electrode 6 was prepared in the same manner as for negative electrode 1 described above.
[0099] (Creating Battery 6) Using the prepared negative electrode 6, a battery 6 was prepared in the same manner as the battery 1.
[0100] <Sample 7> (Preparation of negative electrode slurry 7) A negative electrode slurry 7 was prepared in the same manner as the negative electrode slurry 1, except that the hydrophobized CeNF (dispersed in water, acid value: 76.5 mg / g) in the negative electrode slurry 1 was changed from 0.5 wt% to 0.3 wt%. Note that the hydrophobized CeNF is not counted as a solid component because it is 1 wt% or less, but the solid component including the hydrophobized CeNF may be calculated as 100 wt%.
[0101] (Preparation of negative electrode 7) Negative electrode 7 was prepared in the same manner as for negative electrode 1 described above.
[0102] (Creating Battery 7) Using the produced negative electrode 7, a battery 7 was produced in the same manner as the battery 1.
[0103] <Sample 8> (Preparation of negative electrode slurry 8) Negative electrode slurry 8 was prepared in the same manner as negative electrode slurry 1 and 7, except that the amount of hydrophobized CeNF (dispersed in water, acid value: 76.5 mg / g) in the negative electrode slurry 1 described above was changed from 0.5 wt % to 0.25 wt %.
[0104] (Preparation of negative electrode 8) Negative electrode 8 was prepared in the same manner as in the case of negative electrode 1 described above.
[0105] (Creating Battery 8) Using the produced negative electrode 8, a battery 8 was produced in the same manner as the battery 1.
[0106] <Sample 9> (Preparation of negative electrode slurry 9) A negative electrode slurry 9 was prepared in the same manner as the negative electrode slurry 2, except that the hydrophobized CeNF of the negative electrode slurry 1 described above was replaced with non-hydrophobized CeNF (also referred to as untreated CeNF).
[0107] (Preparation of negative electrode 9) Negative electrode 9 was prepared in the same manner as for negative electrode 1 described above.
[0108] (Creating Battery 9) Using the prepared negative electrode 9, a battery 9 was prepared in the same manner as the battery 1.
[0109] <Sample 10> (Preparation of negative electrode slurry 10) A negative electrode slurry 10 was prepared in the same manner as the negative electrode slurry 2, except that the hydrophobized CeNF of the negative electrode slurry 1 described above was not added.
[0110] (Preparation of negative electrode 10) Negative electrode 10 was prepared in the same manner as negative electrode 1 described above.
[0111] (Preparation of Battery 10) Using the produced negative electrode 10, a battery 10 was produced in the same manner as the battery 1.
[0112] <Sample 11> (Preparation of negative electrode slurry 11) A negative electrode slurry 11 was prepared in the same manner as the negative electrode slurry 6, except that the ratio of graphite to nano-Si in the negative electrode slurry 1 was adjusted to 8:2.
[0113] (Preparation of negative electrode 11) Negative electrode 11 was prepared in the same manner as for negative electrode 1 described above.
[0114] (Creating Battery 11) Using the produced negative electrode 11, a battery 11 was produced in the same manner as the battery 1.
[0115] [Table 1]
[0116] (Initial characteristics) The initial characteristics of the coin-type batteries (samples 1, 2, 5, and 6) produced were examined in an environment of 30° C., with a battery voltage range of 1 mV to 1 V and a constant current of 0.46 mA. Figure 8 is a graph showing the initial characteristics of the coin-type batteries (samples 1, 2, 5, and 6). The horizontal axis is capacity (Capacity, (mAh / g)), and the vertical axis is voltage (E, (V)).
[0117] As shown in FIG. 8, all samples showed good initial characteristics. It was found that the capacity increased as the amount of binder (PI dissolved in NMP) increased from 5 wt% to 7 wt% to 9 wt% to 11 wt%. Usually, when the amount of binder is increased, the capacity tends to decrease. In contrast, the opposite tendency was confirmed in the above sample of this embodiment, so it can be considered that the combination of the binder (PI dissolved in NMP) and hydrophobized CeNF (dispersed in water) suppressed the expansion and contraction of nano-Si accompanying charge and discharge, and improved battery capacity was observed. Note that FIG. 9 is a graph showing the initial characteristics in the case of battery 4 using an aqueous solvent. In the case of battery 4 using this aqueous binder, the battery capacity was lower than any of the above samples 1, 2, 5, and 6. Note that in battery 4, a part without defects in the coating layer was used when visually inspected.
[0118] (Cycle characteristics) The cycle characteristics of the coin type batteries (samples 1, 2, 5, and 6) prepared were examined at a constant current of 0.46 mA in a battery voltage range of 1 mV to 1 V in an environment of 30° C. Figure 10 is a graph showing the cycle characteristics of the coin type batteries (samples 1, 2, 5, and 6). The horizontal axis is the cycle number, and the vertical axis is the discharge capacity (mAh / g).
[0119] As shown in FIG. 10, all of the samples (samples 1, 2, 5, and 6) showed good discharge capacity even when the number of cycles increased. All of the samples (samples 1, 2, 5, and 6) showed better discharge capacity than sample 10, which did not contain CeNF. In addition, there was no significant difference in cycle characteristics when the binder (PI dissolved in NMP) was added in amounts of 5 wt% and 7 wt%, but the cycle characteristics were better for the sample with an addition amount of 11 wt% than for the sample with an addition amount of 9 wt%, and the cycle characteristics of the sample with an addition amount of 11 wt% were the best among samples 1, 2, 5, 6, and 10. Here, samples with a uniform amount of hydrophobic CeNF added of 0.5 wt% were compared, so it is considered that a more effective battery can be obtained depending on the ratio of the binder (PI dissolved in NMP) and the hydrophobic CeNF.
[0120] 11 is a graph showing the cycle characteristics of coin-type batteries (samples 2, 7, and 8) with different amounts of hydrophobic CeNF added. The horizontal axis is the cycle number, and the vertical axis is the discharge capacity (mAh / g).
[0121] As shown in Fig. 11, all of the samples showed better discharge capacity than sample 10, which did not contain CeNF, and sample 9, which used untreated CeNF. As the amount of hydrophobized CeNF added increased from 0.25wt% to 0.3wt% to 0.5wt%, the capacity increased, and the decrease in discharge capacity with increasing cycle number was also small.
[0122] In addition, in the above samples (samples 2, 7, and 8), the ratio of nano-Si was 10% by weight, but the cycle characteristics were examined for samples 3 and 11, in which the ratio of nano-Si was 20%.
[0123] Fig. 12 is a graph showing the cycle characteristics of coin-type batteries (samples 3 and 11) in which the ratio of nano-Si was 8:2. The horizontal axis is the cycle number, and the vertical axis is the discharge capacity (mAh / g).
[0124] As shown in Figure 12, all of the samples showed better discharge capacity than sample 10, which did not contain CeNF, and sample 9, which used untreated CeNF. The discharge capacity improved as the proportion of nano-Si increased. It was also confirmed that the capacity of samples 3 and 11 increased as the amount of binder (PI dissolved in NMP) increased from 9wt% to 11wt%.
[0125] (Consideration) From the above examples and other experiments by the inventors, a better composition for the negative electrode slurry will be considered below.
[0126] As a slurry for a negative electrode containing nano-Si, it is preferable to use hydrophobized CeNF and an organic solvent-based binder.
[0127] The amount of hydrophobized CeNF added is preferably 0.25wt% or more, and it has been found that good results can be obtained even in the range of 0.25 to 0.5wt%. The hydrophobized CeNF may be dispersed in an aqueous solvent. As described above, nano-Si can react with water, but the amount of hydrophobized CeNF added is, for example, less than that of a binder, and the amount of the solvent (dispersion medium) is also small. Therefore, the water in the hydrophobized CeNF dispersed in water does not have an adverse effect. The concentration of hydrophobized CeNF in the aqueous dispersion is, for example, 0.05 to 1wt%. The amount of addition is about 0.05 to 1ml with respect to the total amount of the solvent of the negative electrode slurry, 100ml, and is preferably 1wt% or less of the total amount of the solvent of the negative electrode slurry.
[0128] The content of the hydrophobized CeNF in the negative electrode slurry is preferably 0.01 wt % or more, and more preferably 0.02 wt % or more, based on the solid components (total amount of the negative electrode active material and the binder).
[0129] In addition, good results were obtained when the ratio of graphite to nano-Si in the negative electrode slurry was 9:1 to 8:2. This shows that good results can be obtained even if the ratio of nano-Si in the negative electrode active material is 10 to 20% (8.7 to 17.8 wt% in the above examples).
[0130] It was also found that good results could be obtained even when the amount of organic solvent binder added was 5 to 11 wt % of the solid component of the negative electrode slurry (negative electrode mixture).
[0131] In the above examples, the slurry, electrodes, and batteries are formed in the atmosphere. As described above, a small amount of water-based solvent may be used, and the influence of moisture in the atmosphere is small. Therefore, the formation of the slurry, electrodes, and batteries in this embodiment does not need to be performed in a dry space where humidity and temperature are strictly controlled, and they can be formed in the atmosphere, which is very useful.
[0132] (Embodiment 2) In the example of the first embodiment, a coin-type battery was produced, but there is no limitation on the battery structure to which the negative electrode described in the first embodiment can be applied, and the negative electrode can be used, for example, as the negative electrode of a cylindrical battery. FIG. 13 is a cross-sectional perspective view showing the structure of a cylindrical lithium-ion battery. The lithium-ion battery shown in FIG. 13 has a cylindrical can 106, and the can 106 contains an electrode group in which a strip-shaped positive electrode 101 and a strip-shaped negative electrode 103 are wound with a separator SP interposed therebetween. For example, the strip-shaped positive electrode 101 and the strip-shaped negative electrode 103 have electrode mixture layers formed on both sides of the current collector. In addition, the positive electrode current collector tab on the upper end surface of the electrode group is joined to the positive electrode cap. The negative electrode current collector tab on the lower end surface of the electrode group is joined to the bottom of the can 106. An insulating coating (not shown) is provided on the outer periphery of the can 106. An electrolyte (not shown) is poured into the can 106. Although a cylindrical battery has been described here as an example, a square battery may also be used.
[0133] In the above embodiment, polyimide (PI) was used as the binder, but other organic solvent binders may be used. As the organic solvent binder, it is preferable to use the above polyimide (PI) or polyvinylidene fluoride (PVdF) from the viewpoint of improving the adhesiveness of nano-Si.
[0134] (Embodiment 3) In the first embodiment, the negative electrode slurry is prepared using a stirrer such as a Homodisper, but the negative electrode slurry may be prepared using an extruder.
[0135] Fig. 14 is a cross-sectional view showing a method for preparing a negative electrode slurry using an extruder. As shown in Fig. 14, the extruder has a cylinder 111 and a screw SC arranged inside the cylinder 111. A screw drive unit (not shown) is connected to the screw SC. The cylinder 111 is provided with three supply ports 113a, 113b, and 113c from the upstream side of the cylinder 111. In addition, a discharge nozzle 119 is provided at the tip of the cylinder 111.
[0136] For example, a negative electrode active material (e.g., graphite, nano-Si, other negative electrode active material) is added from the supply port 113a, and while mixing is performed by rotating the screw SC, an organic solvent binder, an organic solvent, and hydrophobized CeNF (dispersed in water) are added from the supply port 113b. Next, alcohol (preparation solvent) is added from the supply port 113c, and mixing is performed by rotating the screw SC. In this way, a negative electrode slurry is prepared and discharged from the discharge nozzle 119.
[0137] A similar extruder can also be used to prepare a positive electrode slurry. FIG. 15 is a cross-sectional view showing a method for preparing a positive electrode slurry using an extruder. For example, a binder and an additive are added from a supply port 113a, and while mixing is performed by rotating the screw SC, an organic solvent (e.g., NMP) is added from a supply port 113b. Next, a positive electrode active material is further added from a supply port 113c, and mixed by rotating the screw SC. In this way, a positive electrode slurry is prepared and discharged from a discharge nozzle 119.
[0138] (Embodiment 4) In the first embodiment, an aqueous solvent (water and / or alcohols, etc., here water (H2O)) is used as a dispersion solvent for the hydrophobized CeNFs, but an organic solvent may also be used. As described above, the hydrophobized CeNFs are preferably used in a state dispersed in a solvent in order to prevent aggregation and increase dispersibility in the slurry. Here, a method for obtaining hydrophobized CeNFs dispersed in an organic solvent by replacing the aqueous solvent of the hydrophobized CeNFs dispersed in an aqueous solvent with an organic solvent will be described.
[0139] (Preparation method of hydrophobized CeNF dispersed in organic solvent) 16 is a diagram showing the preparation process of hydrophobized CeNFs dispersed in an organic solvent. Here, a method for preparing NMP-dispersed hydrophobized CeNFs is described in which NMP is used as the organic solvent and succinic anhydride is used as the carboxylic acid compound that is the hydrophobizing agent.
[0140] As shown in Fig. 16(A), cellulose (solid, e.g., powder) and succinic anhydride (solid, e.g., tablet) are mixed at 100°C or higher. For example, they are mixed for 20 minutes at 125°C using a pressure kneader. The weight ratio of cellulose to succinic anhydride is, for example, 90wt% and 10wt%.
[0141] The mixture is stirred under heating as described above, and an ester reaction occurs to produce hydrophobic cellulose. After this, the mixture is washed with acetone or the like to remove unreacted succinic anhydride.
[0142] Next, the produced hydrophobic cellulose is dispersed in an aqueous solvent (water and / or alcohols, etc., here water (H2O)) and subjected to a micronization process (fibrillation process, nanoization). For example, a micronization device (Starburst) is used to perform a process at 245 MPa and 10 passes to nanonize the cellulose. Up to this point, the process is the same as the preparation method of hydrophobic CeNF dispersed in an aqueous solvent described with reference to FIG. 3. This allows hydrophobic CeNF to be obtained. Here, the hydrophobic CeNF at this stage is in a state of being dispersed in an aqueous solvent, and this aqueous solvent is replaced with NMP (organic solvent). For example, as shown in FIG. 16(B), the aqueous solvent (here water (H2O)) is gradually replaced with an organic solvent (here NMP) using a rotary evaporator.
[0143] First, an organic solvent (e.g., NMP) is added to the aqueous solvent in which the hydrophobized CeNFs are dispersed to form a mixed solution. In this case, the mixed solution is prepared so that the hydrophobized CeNFs (solid content) are 0.1 to 20 wt% when the solvent is 100 wt%. In this way, the CeNFs dispersed in the organic solvent (e.g., NMP) can be obtained.
[0144] Next, while stirring the mixed solution, the aqueous solvent (here, water (H2O)) is evaporated and removed from the mixed solution to increase the concentration of the organic solvent (here, NMP).
[0145] The invention made by the present inventor has been specifically described above based on the embodiment and examples. However, the present invention is not limited to the above embodiment or examples, and it goes without saying that various modifications can be made without departing from the gist of the invention. [Explanation of symbols]
[0146] 1M Negative electrode mixture layer 1S current collector 1T negative terminal 2M Positive electrode mixture layer 2S current collector 2T positive terminal 20 Application section 30 Drying section 101 Positive electrode 103 Negative electrode 106 cans 111 Cylinder 113a Supply port 113b Supply port 113c Supply port 119 Discharge Nozzle B Valve D Slit Die P-Pump R Roll S base material SC screw SL Negative electrode slurry SP Separator T Coating fluid tank UW Unwinding section WD Winding section
Claims
1. a negative electrode mixture including a negative electrode active material, a binder, and hydrophobized cellulose; The negative electrode active material contains Si particles, The binder is an organic solvent-based binder, The hydrophobized cellulose is a cellulose in which a part of the hydrophilic groups is replaced with a hydrophobic group, The negative electrode for a lithium ion battery, wherein the Si particles are nanoparticles.
2. 2. The negative electrode for a lithium ion battery according to claim 1, The negative electrode for a lithium ion battery, wherein the average particle size of the Si particles is 10 nm or more and 500 nm or less.
3. 3. The negative electrode for a lithium ion battery according to claim 2, 13. A negative electrode for a lithium ion battery, wherein the organic solvent-based binder is polyimide or polyvinylidene fluoride.
4. 4. The negative electrode for a lithium ion battery according to claim 3, The negative electrode for a lithium ion battery, wherein the hydrophobized cellulose is hydrophobized with a carboxylic acid compound.
5. The negative electrode for a lithium ion battery according to claim 4, The hydrophobized cellulose has a particle shape having a length of 3 nm or more and 10 μm or less and an aspect ratio (length / diameter) of 0.01 or more and 10,000 or less.
6. A lithium ion battery comprising: a negative electrode having a current collector and a negative electrode mixture layer formed on the current collector; a positive electrode; and an electrolyte solution, The negative electrode mixture layer contains a negative electrode active material, a binder, and hydrophobized cellulose, The negative electrode active material contains Si particles, The binder is an organic solvent-based binder, The hydrophobized cellulose is a cellulose in which a part of the hydrophilic groups is replaced with a hydrophobic group, The lithium ion battery, wherein the Si particles are nanoparticles.
7. 7. The lithium ion battery according to claim 6, The lithium ion battery, wherein the average particle size of the Si particles is 10 nm or more and 500 nm or less.
8. 8. The lithium ion battery according to claim 7, The organic solvent-based binder is polyimide or polyvinylidene fluoride.
9. 9. The lithium ion battery according to claim 8, The lithium ion battery, wherein the hydrophobized cellulose is hydrophobized with a carboxylic acid compound.
10. 10. The lithium ion battery according to claim 9, A lithium ion battery, wherein the particle shape of the hydrophobized cellulose has a length of 3 nm or more and 10 μm or less and an aspect ratio (length / diameter) of 0.01 or more and 10,000 or less.
11. (a) mixing a negative electrode active material, a binder, and hydrophobized cellulose to form a negative electrode slurry; (b) applying the negative electrode slurry onto a current collector; having The negative electrode active material contains Si particles, The binder is an organic solvent-based binder, The hydrophobized cellulose is a cellulose in which a part of the hydrophilic groups is replaced with a hydrophobic group, The method for producing a negative electrode for a lithium ion battery, wherein the Si particles are nanoparticles.
12. 12. The method for producing a negative electrode for a lithium ion battery according to claim 11, The step (b) comprises: (b1) applying a negative electrode slurry to a first surface of the substrate removed from the discharge section; (b2) drying the negative electrode slurry on the substrate to form a negative electrode mixture layer on a first surface of the substrate; (b3) taking in the base material on which the negative electrode mixture layer is formed in a carry-in section; A method for producing a negative electrode for a lithium ion battery comprising the steps of:
13. 13. The method for producing a negative electrode for a lithium ion battery according to claim 12, The method for producing a negative electrode for a lithium ion battery, wherein the average particle size of the Si particles is 10 nm or more and 500 nm or less.
14. 14. The method for producing a negative electrode for a lithium ion battery according to claim 13, The method for producing a negative electrode for a lithium ion battery, wherein the organic solvent binder is polyimide or polyvinylidene fluoride.
15. 15. The method for producing a negative electrode for a lithium ion battery according to claim 14, The method for producing a negative electrode for a lithium ion battery, wherein the hydrophobized cellulose is hydrophobized with a carboxylic acid compound.
16. (a) preparing a negative electrode slurry; (b) applying the negative electrode slurry onto a current collector to form a negative electrode having the current collector and a negative electrode mixture layer; (c) forming an electrode group in which the negative electrode and the positive electrode are stacked with a separator interposed therebetween; (d) housing the electrode group in a battery container; (e) after the step (d), injecting an electrolyte into the battery container; having The step (a) is a step of mixing a negative electrode active material, a binder, and a hydrophobized cellulose to form a negative electrode slurry, The negative electrode active material contains Si particles, The binder is an organic solvent-based binder, The hydrophobized cellulose is a cellulose in which a part of the hydrophilic groups is replaced with a hydrophobic group, The method for producing a lithium ion battery, wherein the Si particles are nanoparticles.
17. 17. The method for producing a lithium ion battery according to claim 16, The step (b) comprises: (b1) applying a negative electrode slurry to a first surface of the substrate removed from the discharge section; (b2) drying the negative electrode slurry on the substrate to form a negative electrode mixture layer on a first surface of the substrate; (b3) taking in the base material on which the negative electrode mixture layer is formed in a carry-in section; A method for manufacturing a lithium ion battery comprising the steps of:
18. 18. The method for producing a lithium ion battery according to claim 17, The method for producing a lithium ion battery, wherein the average particle size of the Si particles is 10 nm or more and 500 nm or less.
19. 19. The method for producing a lithium ion battery according to claim 18, The method for producing a lithium ion battery, wherein the organic solvent binder is polyimide or polyvinylidene fluoride.
20. 20. The method for producing a lithium ion battery according to claim 19, The method for producing a lithium ion battery, wherein the hydrophobized cellulose is hydrophobized with a carboxylic acid compound.
Citation Information
Patent Citations
High capacity anode electrode with mixed binder for energy storage devices
JP2018529206A
Substrate handling device, exposure device, method for producing flat panel display, device production method, substrate handling method, and exposure method
WO2019064583A1
Non-aqueous electrolyte secondary battery and method for manufacturing non-electrolyte secondary battery
WO2020090014A1